2015
DOI: 10.1097/md.0000000000001345
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine Compared With Gemcitabine and S-1 Combination Therapy in Advanced Pancreatic Cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…However, subgroup analysis showed that GEM plus CAP and GEM plus S-1 could effectively improve OS, PFS, and ORR, but GEM plus CIS did not achieve the same effect. Li et al's meta-analysis compared the effects of GEM plus fluorouracil-based drugs (CAP and S-1) with GEM alone in advanced pancreatic cancer, and they concluded that compared with GEM alone, GEM combined with fluorouracil significantly improved OS and increased 1-year survival and ORR in patients with advanced pancreatic cancer (43). Zhou et al's meta-analysis compared the effects of GEM plus CIS and GEM alone in advanced pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, subgroup analysis showed that GEM plus CAP and GEM plus S-1 could effectively improve OS, PFS, and ORR, but GEM plus CIS did not achieve the same effect. Li et al's meta-analysis compared the effects of GEM plus fluorouracil-based drugs (CAP and S-1) with GEM alone in advanced pancreatic cancer, and they concluded that compared with GEM alone, GEM combined with fluorouracil significantly improved OS and increased 1-year survival and ORR in patients with advanced pancreatic cancer (43). Zhou et al's meta-analysis compared the effects of GEM plus CIS and GEM alone in advanced pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer is a lethal malignancy with a modest response to systemic chemotherapy [21]. Although GS treatment is associated with a higher response rate [14], and better PFS [14] and OS [22] than gemcitabine in APC [19,20], a substantial proportion of our patients still had progressive disease and, therefore, were exposed to unnecessary toxicity. Using patients’ clinical variables in conjunction with their laboratory test values, we developed a prognostic model for the prediction of survival outcomes in patients with APC who underwent palliative chemotherapy with GS.…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analysis studies indicate that GEM/S-1 combination therapy, as a first-line treatment, may be more effective at increasing survival rates in patients with unresectable pancreatic cancer (5,24). Qing-Hua et al showed that GEM/S-1 combination therapy followed by oral S-1 with intensity-modulated radiotherapy (IMRT) protocol achieved a 2-year survival rate of 34.4%, which was similar to the results we have outlined in this study (2-year survival rate of 33.3%) (11).…”
Section: Discussionmentioning
confidence: 99%